2008
DOI: 10.2174/157019308786242223
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization, Biological Effects, and Synthetic Studies on Xanthones from Mangosteen (Garcinia mangostana), a Popular Botanical Dietary Supplement

Abstract: Mangosteen (Garcinia mangostana L., Clusiaceae) is a popular botanical dietary supplement in the United States, where it is used principally as an antioxidant. It is referred to as the “queen of fruits” in Thailand, a country of origin. The major secondary metabolites of mangosteen, the xanthones, exhibit a variety of biological activities including antibacterial, antifungal, antiinflammatory, antioxidant, antiplasmodial, cytotoxic, and potential cancer chemopreventive activities. Moreover, some of the xanthon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
100
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 61 publications
0
100
0
2
Order By: Relevance
“…AlCl 3 formed complex with hydroxyl groups and neighboring ketone (C-4 in ring C and C-5 on ring A). 7 This result was supported by UV-Vis spectrum. 8 The UV spectrum formed two bands on λ 355 and 275 nm which can be deduced that the isolate was flavonoid.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…AlCl 3 formed complex with hydroxyl groups and neighboring ketone (C-4 in ring C and C-5 on ring A). 7 This result was supported by UV-Vis spectrum. 8 The UV spectrum formed two bands on λ 355 and 275 nm which can be deduced that the isolate was flavonoid.…”
Section: Discussionmentioning
confidence: 52%
“…According to the research conducted by Chin and Kinghorn 2008, β-mangostin showed inhibitory activity against HIV-1 RT of 42 %. 7 Morus alba has an inhibitory activity of 98.45 % by the morusin content. Psidium guajava has the inhibitory activity of 97.21 % associated with the content of quercetin and guajiverin.…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has demonstrated that ISL has a variety of pharmacological activities, such as antioxidant, vasorelaxant, anti-inflammatory, estrogenic, and antiplatelet aggregation effects [7][8][9]. In addition, some studies have proven that ISL also possesses antitumor activity against different cancers, including hepatoma [10], uterine leiomyoma [11], prostate cancer [6,12,13], melanoma [14], gastric cancer [15], and breast cancer [16], but the effects of ISL on osteosarcoma cells are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Garcinia mangostana Linn or commonly known as mangosteen is a plant from Guttiferae family and have been used traditionally for the treatment of skin infections and wound, amoebic dysentery and inflammation (Chaverri et al 2008;Chin & Kinghorn 2008). These plants contain xanthone-type compounds, flavonoids, triterpenoids, benzophenones, biphenyl compounds, pyrrole, benzofuran, tannins, and saponins (Chaverri et al 2008;Hutapea 1994).…”
Section: Introductionmentioning
confidence: 99%